Resurrecting the First Great American Play : Imperial Politics and Colonial Ambitions in Frontier Detroit - Ludwig, Sämi, 1960- (Book collections on Project MUSE., 2020)
"In the mid-eighteenth century, the Ottawa chief Pontiac (often spelled Ponteach at the time) led an intertribal confederacy in resisting British power in the Great Lakes region, an event immortalized in the play Ponteach, or the Savages of America. This play, written by infamous frontier soldier Robert Rogers, is one of the earliest theatrical renderings of the region, depicting its hero in a way that called into question eighteenth-century constructions of Indigenous Americans. Sämi Ludwig contends that Ponteach's literary and artistic merits are worthy of further exploration. He investigates the questions of authorship and analyzes the play's content, embracing its many contradictions as enriching windows into the era. In this way, he suggests using Ponteach as a tool to better understand British imperialism in North America and the emerging theatrical forms developing in the Young Republic"--